The negro: the southerner's problem - Page, Thomas Nelson, 1853-1922 (Salt Lake City, UT : Project Gutenberg, 2023)
"The Negro: The Southerner's Problem" by Thomas Nelson Page is a collection of essays written in the early 20th century that addresses the extensive and complex issues surrounding race relations in the post-Civil War American South. Through his writings, Page attempts to explore the historical context of the racial divide, focusing particularly on the consequences of emancipation and the ongoing challenges faced by both black and white communities in the South. The essays reflect Page's views on the inherent complexities and sensitivities involving the narrative of race in America, drawing from his experiences and observations. At the start of the text, the author lays the groundwork for a thorough examination of "The Negro Question," which he identifies as a crucial and long-standing dilemma most notably affecting Southern society. He notes that this topic has been a source of contention and misunderstanding, particularly between Southern whites who live daily with its implications and Northern whites who hold often radical views shaped by sentimental narratives. Page aims to approach this subject with candor, highlighting the historical relationships between races, the impact of slavery, and the failures and successes in attempts at integration and education for the freedmen. Through this introduction, he expresses the hope that his writings might contribute to a more informed and open dialogue about these pressing issues. (This is an automatically generated summary.)
Release date is 2023-05-22
Bob Taylor, Tim Lindell and the Online Distributed Proofreading Team at https://www.pgdp.net (This file was produced from images generously made available by The Internet Archive/American Libraries.)
Keywords: African Americans; United States -- Race relations